State and Trends of the Carbon Market 2003 - Lecocq, Franck (World Bank, Washington, DC, 2013)
The emerging carbon market encompasses both project-based emission reduction transactions, whereby a buyer participates in the financing of a project which reduces greenhouse gases (GHGs) emissions, compared with what would have happened otherwise, and gets some of the emission reductions (ERs) thus generated in return; and, trades of GHG emission allowances allocated under existing, or incoming, cap-and-trade GHG emissions control regimes. This Review of the state and trends of the carbon market as of November 2003, based on material provided by Evolution Markets LLC, Natsource LLC and PointCarbon, and on direct interviews with market participants, suggest that: volume exchanged on the carbon market has more than doubled since 2002; buyers are governments, and public-private partnerships like the Prototype Carbon Fund; in 2003, nine out of ten tones of emission reductions originate from projects located in transition economies or developing countries; prices differ depending on the segment of the market, and on the structure of the transaction; allowance markets dominate in number of transactions, but volume exchanged remains small compared with project-based transactions; and, because of long lead time between project preparation and first "yield" of emission reductions, and absent clarification of the validity of project-based emission reductions beyond 2012, the window of opportunity for project-based transactions is rapidly closing. The report further discusses volumes of GHG Emission Reductions (ERs) up to 2012 only, to provide an idea of the volume that might be available for compliance, since 2012 is the end of the first commitment period of the Kyoto Protocol, and a milestone in most regimes. For projects where vintages 2013 and beyond are purchased (in particular in forestry-related projects), it was assumed an even annual accrual of ERs, unless known otherwise. Also, throughout the paper, volumes are reported in metric tones of CO2 equivalent (tCO2e).